Legal Review Of Granting Of Building Utilization Rights (HGB) For 160 Years To Investors In The Capital City Of The Nusantara Development (IKN) - Abdul Zaini; Muhammad Syihabuddin; Wiranti; Wiwit Wijayanti (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
The purpose of this writing is to understand the policies issued by the Government of Indonesia through the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) offering incentives for building use rights (HGB) for up to 80 years and even up to 160 years for investors in Mrs. Archipelago City (IKN). Laws and regulations regarding the term of building use rights have been regulated in law number 5 of 1960 concerning basic agrarian regulations, other laws and regulations which also regulate building use rights are in Government Regulation Number 18 of 2021 concerning management rights. , Land rights, apartment units and land registration, the HGB period according to this law is given for a maximum period of 30 years, extended for a maximum period of 20 years and renewed for a maximum of 30 years. The research method used in this paper is a type of normative research that analyzes the Granting of Building Use Rights (HGB) for 160 years to Investors for the Development of the Archipelago Capital City (IKN). This normative research emphasizes written documents such as laws and regulations, court decisions, legal theories and opinions of scholars. The granting of Building Use Rights to investors for the development of the Archipelago Capital City cannot be given at the same time, Extension and renewal of HGB for 160 years, but Building Use Rights for 30 (thirty) years are given then extended for 20 (twenty) years, and renewal is carried out for 30 (thirty) years after the expiry of the land with the Right to Build, it will return to become Land directly controlled by the State or Land with Management Rights.